The association between CCR5, NLRC4, and AIM2 gene polymorphisms and susceptibility to tuberculosis in the Iraqi population - BILAL KHALEEL; HUDA R. S. AL-ALWANI; AHMED ASMAR (Society for Indonesian Biodiversity, 2024)
Abstract. Khaleel B, Al-Alwani HRS, Asmar A. 2024. The association between CCR5, NLRC4, and AIM2 gene polymorphisms and susceptibility to tuberculosis in the Iraqi population. Biodiversitas 25: 1022-1029. In immunological reactions against Mycobacterium tuberculosis, chemokines and their receptors, including CXCR3, CCR5, and RANTES, play an important role in the migration and activation of cells. The inflammasome is a multiprotein complex that serves as a master regulator of inflammation. Genetic polymorphisms contribute to individual phenotypic differences, such as disease risk and drug response. The current study was done to find the polymorphism in the CCR5, NLRC4, and AIM2 genes in our population and to look into how this polymorphism is linked to getting tuberculosis. Seventy-five tuberculosis patients participated in this study, while the control group comprised twenty-five control healthy individuals. We took two milliliters of blood from the patients and the control group and placed them in an Ethylenediaminetetraacetic acid (EDTA tube), or DNA extraction. Real-time PCR was used to find changes in the genes for CCR5 (rs2227010, rs2734648, rs1799987, rs1799988, rs1800023, rs1800024), NLRC4 (C-rs479333), and AIM2 (CC-rs1103577). Some genotypes were more common in the patient group, including SNPs CCR5 (rs2227010, rs2734648, rs1799988, rs1800023, rs1800024), NLRC4 C-rs479333, and AIM2 CC-rs1103577. However, by using Two-Two cross table the genotype of SNP CCR5-rs1799987 was not significantly different between the patient and the controls. Patients also had a lot of certain alleles for the SNPs CCR5 (rs2227010, rs1799988, rs1800023, rs1800024) and NLRC4 (rs479333). However, the alleles for the SNPs CCR5 (rs2734648, rs1799987) and AIM2 CC (rs1103577) were not very different between patients and controls. This study concludes that a polymorphism in various SNPs of the CCR5, NLRC4, and AIM2 genes may be a risk factor for tuberculosis.